Monetary Policy in the Philippines During Periods of Financial Crisis and Changes in Exchange Rate Regime : Targets, Instruments, and the Stability of Money Demand. (IMF Working Papers; Working Paper ;, 1989)
This paper examines some of the key issues in the conduct of Philippine monetary policy since 1984, including the various shocks to the economy and the monetary authorities' choice of intermediate policy targets and instruments used to achieve those targets. Against this background, estimates of demand functions for various categories of monetary aggregates and tests of stability are reported. A monetary model of exchange market pressure is also estimated. The results suggest that even after the adoption of a floating exchange rate system, the authorities allowed changes in foreign reserves to continue to absorb most of the exchange market pressure.